Neoehrlichia mikurensis in Danish immunocompromised patients: a retrospective cohort study - Rosa Maja Møhring Gynthersen; Mette Frimodt Hansen; Lukas Frans Ocias; Andreas Kjaer; Randi Føns Petersen; Sisse Rye Ostrowski; Lene Harritshøj; Søren Jacobsen; Ulrik Overgaard; Karen Angeliki Krogfelt; Anne-Mette Lebech; Helene Mens (BMC, 2023)
Abstract Background The tick-borne bacterium, Neoehrlichia mikurensis (N. mikurensis) can cause severe febrile illness and thromboembolic complications in immunocompromised individuals. We investigated the presence of N. mikurensis DNA in retrospectively collected plasma from a well-characterized cohort of Danish immunocompromised patients. Methods Plasma samples from 239 patients with immune dysfunction related to hematological or rheumatological disease or due to immunosuppressive therapy, were retrieved from a transdisciplinary biobank (PERSIMUNE) at Rigshospitalet, Copenhagen, Denmark. Serving as immunocompetent controls, plasma samples from 192 blood donors were included. All samples were collected between 2015 and 2019. Real-time PCR targeting the groEL gene was used to detect N. mikurensis DNA. Sequencing was used for confirmation. Borrelia burgdorferi sensu lato IgG antibodies were detected by ELISA as a proxy of tick exposure. Prevalence was compared using Fisher's exact test. Results Neoehrlichia mikurensis DNA was detected in 3/239 (1.3%, 95% confidence interval (CI): 0.3 - 3.6%) patients, all of whom primarily had a hematological disease. Follow-up samples of these patients were negative. N. mikurensis DNA was not detected in any of the blood donor samples. IgG antibodies against B. burgdorferi s.l. were detected with similar prevalence in immunocompromised patients and blood donors, i.e., 18/239 (7.5%, 95% CI: 4.8-11.5%) and 11/192 (5.7%, 95%: CI 3.2-10.0%). Conclusion In this study, patients with N. mikurensis were not identified by clinical indication and N. mikurensis may therefore be underdiagnosed in Danish patients. Further investigations are needed to explore the clinical significance and implications of this infection.